KONSEP PERKEMBANGAN HUKUM DAGANG DULU, SAAT INI DAN MASA DEPAN - Jumhana, Enjum; Ali, Mohamad (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2023)
Talking about the history of trade law in Indonesia, starting from the history of trade law, namely originating from Dutch law, then Dutch law originating from French law, then French law originating from ancient Roman law. In fact, the Ancient Roman civilization was actually heavily influenced by Middle Eastern Civilization, that both of us from the religions of Islam, Christianity, Buddhism, and Hinduism came from revelations derived from Middle Eastern civilization. It turns out that the development of Roman Law has had a lot of influence from Middle Eastern Law, but if we study the current Commercial Law from the Code de Commerce and the Civil Code which are influenced by Ancient Roman Law. Then because the French State colonized the Netherlands, the Code de Commerce and the Civil Code changed their respective derivatives to become the Civil Code to become the Burgerlijk Wetboek / BW (Dutch Civil Code) and the Code du Commerce to become Wetboek van Koophandel / WvK (Dutch Commercial Law Book). Then Burgerlijk Wetboek / BW (Civil Code) and Wetboek van Koophandel / WvK (KUHD) came into effect in the Dutch East Indies at that time (Indonesia, now) since 1 May 1848.  In the Netherlands itself BW and WvK came into force since 1 October 1838. After Indonesia independence, the Civil Code and the Criminal Code were declared valid to fill the legal vacuum at that time. And the basis for its entry into force is Article II of the Transitional Rules of the 1945 Constitution before it is amended. In the Netherlands itself since independence from French colonialism in 1813, Burgerlijk Wetboek / BW and Wetboek van Koophandel / WvK came into effect